On the Stability of One-Dimensional Wave Equation. (27th October 2013) - Jung, Soon-Mo
Abstract : We prove the generalized Hyers-Ulam stability of the one-dimensional wave equation, u t t = c 2 u x x, in a class of twice continuously differentiable functions.